2005
DOI: 10.1074/jbc.m501630200
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylyl Cyclase-activating Polypeptide 38 Reduces Astroglial Proliferation by Inhibiting the GTPase RhoA

Abstract: Pituitary adenylyl cyclase-activating polypeptide 38 (PACAP38) plays an important role in the proliferation and differentiation of neural cells. In the present study, we have investigated how PACAP38 inhibits the proliferation of cultured neocortical astroglial cells. When applied to synchronized cells during the G 1 phase of the cell cycle, PACAP38 diminished the subsequent nuclear uptake of bromodeoxyuridine. When applied for 2 days, it reduced the cell number. PACAP38 did not exert its antiproliferative eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…However, when Rho-kinase was inhibited with Y27632 (10μM), Reelin was also capable to increase the number of axonal branches (Figure 5B); Y27632 alone did not influence the number of axonal branches compared to controls. The neuropeptides vasoactive intestinal peptide (VIP) and pituitary-adenylyl-cyclase-activating polypeptide-38 (PACAP38), which have an established role in neuronal development (Dickson and Finlayson, 2009; Waschek, 2002; Vaudry et al, 2009) can activate Cdc42 and Rac1, but also decrease RhoA and Rho-kinase activity in neural cells (Meyer et al, 2005; Henle et al, 2006). As VIP-mediated Rho-kinase inhibition induces the elongation of dendrites and axons by stabilizing microtubules (Leemhuis et al, 2007) we used VIP alone and in combination with Reelin.…”
Section: Resultsmentioning
confidence: 99%
“…However, when Rho-kinase was inhibited with Y27632 (10μM), Reelin was also capable to increase the number of axonal branches (Figure 5B); Y27632 alone did not influence the number of axonal branches compared to controls. The neuropeptides vasoactive intestinal peptide (VIP) and pituitary-adenylyl-cyclase-activating polypeptide-38 (PACAP38), which have an established role in neuronal development (Dickson and Finlayson, 2009; Waschek, 2002; Vaudry et al, 2009) can activate Cdc42 and Rac1, but also decrease RhoA and Rho-kinase activity in neural cells (Meyer et al, 2005; Henle et al, 2006). As VIP-mediated Rho-kinase inhibition induces the elongation of dendrites and axons by stabilizing microtubules (Leemhuis et al, 2007) we used VIP alone and in combination with Reelin.…”
Section: Resultsmentioning
confidence: 99%
“…We could demonstrate that Reelin functionally interacts with the peptidergic VIP/PACAP38-receptor system to increase axonal branch formation. 24 As VIP-mediated Rho-kinase inhibition 35,36 induces the elongation of dendrites and axons by stabilizing microtubules, 37 these results demonstrate that Reelin and a neuropeptidergic system can cooperate to promote neuronal development by inducing axonal branching. In addition, these findings pinpoint the influence of the tubulin cytoskeleton in mediating Reelin's effect on neuromorphogenesis, which is also targeted by other effectors of the Reelin-Dab1 signaling cascade, including the Tau kinase GSK3beta, 12 Lis1, 38 and Map1b.…”
Section: Reelin and Neuropeptidergic Signaling Converge On The Level mentioning
confidence: 90%
“…Activation and/or inactivation of Rho proteins in other glial cell types such as astrocytes, Schwann, and Bergmann cells have demonstrated that small GTPases may be important factors for polarity, motility, maintenance of morphology, and proliferation (Manning et al, 1998;Ramakers and Moolenaar, 1998;Etienne-Manneville and Hall, 2001;Kaartinen et al, 2001;Sepp and Auld, 2003;Guasch et al, 2003;Meyer et al, 2005). However, little is known about the expression and role of Rho GTPases, particularly RhoB, and the regulation of cellular morphology in vertebrate retina Mü ller cell.…”
mentioning
confidence: 96%